Papua New Guinea food price bulletin: July 2023 - International Food Policy Research Institute; Hayoge, Greg; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2023)
Download time series food price data, and build graphs and tables for over 20 different food crops at our food price database webpage: https://www.ifpri.org/project/freshfood-price-analysis-papua-new-guinea. Price trends in Q2, 2023Staple Crops: Between Q1 and Q2, the price of sweet potato declined 19 percent (except in Lae, up 30 percent), taro decreased 5 percent (except Lae and Banz, up 11 percent), cassava fell 8 percent (except Goroka, up 17 percent), and cooking banana cooking decreased 14 percent (except Lae and Banz, up 16 and 5 percent, respectively). Vitamin-dense foods: On average, vegetable (aibika, choko-tips, English cabbage, carrot, and capsicum) prices increased 15 percent between Q1 and Q2, except in Goroka, Kokopo, and Mt Hagen, where the price of aibika, English cabbage, and carrot decreased by 8 percent. Fresh Fruits: Lemon and orange prices decreased 15 percent and 8 percent between Q1 and Q2, while ripe banana, watermelon, and pawpaw slightly increased by 4 percent. Compared to other markets, the price of oranges and lemons are expensive in Port Moresby at 11.5 PGK/kg and 7.6 PGK/kg, respectively. Banz, Mt Hagen, and Goroka experienced average price increases in ripe banana, pawpaw, and watermelon of 21, 14 and 21 percent, respectively.